HUBUNGAN PEMILIHAN AKSES VASKULAR DENGAN KUALITAS HIDUP PASIEN CKD HD REGULER DI RUANG HEMODIALISIS RSUD Dr. HARYOTO LUMAJANG - Dyah Esti Pratiwi; Suhari Suhari; Alwin Widhiyanto (NHM PRESS, 2023)
Hemodialysis is a medical treatment to replace kidney function when is in trouble. Hemodialysis which is performed regularly, should provide comfort to the patient Comfort can improve the quality of life for patients who routinely undergo hemodialysis, including the selection of vascular access for hemodialysis patients. The aim of this study was to determine the relationship between the choice of vascular access and quality of life for patients undergoing hemodialysis. This research is a quantitative study using cross sectional correlation method design. The population of this study were all regular CKD HD patients in the hemodialysis room at Dr. Haryoto Lumajang with a total of 144 patients. The samples were 132 respondets taken using total sampling technique who met the inclusion criteria. The data collection the WHOQOL-BREF (The World Health Organization Quality of Life) questionnaire. The Data analyzed using the Spearman Rank Test. The results obtained showed that most of the respondents used vascular AV shunt access of 63.6% and most of the quality of life of hemodialysis patients was good, 52.3% with a significance value of 0.000 (p <0.05) meaning that there is a relationship between the selection of vascular access using the AV shunt method and the patient's quality of life. The Spearman correlation value indicates that vascular access has a sufficient correlation (0.350) and indicates a positive correlation direction. where the AV shunt vascular access shows the patient's quality of life to be good. Based on the results of this study, it is hoped that it can add to and increase knowledge about the quality of life of patients undergoing hemodialysis therapy, especially for hemodialysis patients based on vascular access